Improving Student Success with Online Embedded Tutor Support in First-Year Subjects. - Linden, Kelly; Teakel, Sarah; Van der Ploeg, Neil (Student Success v.13 n.2 p.42-50 https://doi.org/10.5204/ssj.2338, 2022)
Institutional commitment to the student experience in the early stages of university has the greatest potential to exceed student expectations. The cross-institutional Embedded Tutors Program provides undergraduate students with access to subject content experts from 12 first-year subjects across a regional university. Tutors provide one-on-one draft assessment feedback in subjects with a large written assessment task. A total of 428 students attended 615 tutor sessions held online via Zoom. Students who met with a tutor had higher average assessment marks and cumulative subject marks than those students who did not attend a session. Feedback from students was positive, with 78% of students rating the tutor session “extremely helpful.” This study provides evidence of the value of subject-specific draft assessment feedback for students in first-year subjects. [Abstract]